2013
DOI: 10.1155/2013/353695
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Gold Nanoparticles in Several Rat Organs after Intraperitoneal AdministrationIn Vivo: A Fluorescence Study

Abstract: Background. The gold nanoparticles (GNPs) have potential applications in cancer diagnosis and therapy. In an attempt to characterise the potential toxicity or hazards of GNPs as a therapeutic or diagnostic tool, the fluorescence spectra in several rat organs in vivo were measured after intraperitoneal administration of GNPs. Methods. The experimental rats were divided into control and six groups (G1A, G1B, G2A, G2B, G3A, and G3B; G1: 20 nm; G2: 10 nm; G3: 50 nm; A: infusion of GNPs for 3 days; B: infusion of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In this study, it was observed that MgO NPs and MPs significantly enhanced the enzyme levels of ALP, AST, and ALT in serum as well as liver and kidney homogenates of treated rats and was dose but not gender dependent. Increased levels of these enzymes in the tissue homogenates may be due to the extent of hepatocellular injury leading to possible leakage of these enzymes into the bloodstream . A study by Easo et al reported functional integrity of cell membrane would be lost resulting in perturbation of transport function of hepatocytes causes tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed that MgO NPs and MPs significantly enhanced the enzyme levels of ALP, AST, and ALT in serum as well as liver and kidney homogenates of treated rats and was dose but not gender dependent. Increased levels of these enzymes in the tissue homogenates may be due to the extent of hepatocellular injury leading to possible leakage of these enzymes into the bloodstream . A study by Easo et al reported functional integrity of cell membrane would be lost resulting in perturbation of transport function of hepatocytes causes tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Regardless of the NP delivery mechanisms used, uptake by the reticuloendothelial system (RES), particularly the liver, spleen, and kidney, prevent up to 90% of systemically injected NPs from successfully reaching the tumor. [44][45][46][47][48][49] New approaches in NP conjugation technology are needed to optimize NP delivery to the tumor. Further, to our knowledge, many studies using NP-enabled NIR photothermal therapy have not included a rigorous histological analysis of treated tumors, thus creating a knowledge gap of the effect of photothermal therapy at the cellular level.…”
Section: Green Et Almentioning
confidence: 99%
“…55 Intraperitoneal injection may cause a higher accumulation of AuNPs in kidneys compared with micromolecules. 56 As revealed by the TEM images, the NiNPs used here were spherical. Previously, when a comparison between cubic, spherical and rod-like gold nanoparticles was made, spherical particles showed the highest cellular uptake.…”
Section: Discussionmentioning
confidence: 85%